Active disassembly of polymeric components - Ong, Gerry En Zhi (2015)
Shape memory polymers (SMP) have been used in different applications in many industries. SMP are materials that are able to recover its original shape in the presence of an external stimulus, which include heat, application of magnetic field, mechanical force, etc. This report will document, the theories and concepts behind the mechanisms of the shape memory effect (SME) in SMP. It will also give an introduction to active disassembly, which uses the mechanism of the SME. In this project, two engineering polymers are studied, namely hydrogel and ethylene-vinyl acetate (EVA). Based on the glass-transition temperature (Tg) and melting temperature (Tm), various experiments were carried to show that Hydrogel and EVA are SMP that are based on the presence of a heat stimulant. Active disassembly of the two polymers was also shown through further experiments. A potential application utilizing the ability of EVA to recover its shape is also presented.